Indonesia and Turkey's Economic Diplomacy in Enhancing Economic Cooperation: IT-CEPA Case Study - Almira Della; Ade Solihat (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This article discusses Indonesia and Turkey's diplomacy in enhancing economic cooperation, a case study of the Indonesia-Turkey Comprehensive Economic Partnership Agreement (IT-CEPA). Globalization is very influential in the development of the country's economy. In increasing Indonesia's competitiveness, it cannot be separated from the regional or global level. The global economic slowdown in 2015 also had a major impact on the Indonesian economy, particularly in the trade sector. To improve the country's economy, Indonesia understands with Turkey in the Indonesia-Turkey Comprehensive Economic Partnership Agreement (IT-CEPA) which has been going on for four rounds since it was signed in 2017. This article is compiled from qualitative research and aims to explain how economic diplomacy between Indonesia and Turkey is established through the Indonesia-Turkey Comprehensive Economic Partnership Agreement (IT-CEPA). The data is obtained through previous case studies and enriched with writings related to Indonesia's economic diplomacy obtained from books, scientific articles and popular articles accessed through the internet.